Shifting Death Penalty as Main Punishment towards Alternative Punishment: An Effort to Realize the Middle Way of Human Rights - Handrawan; Dewi Ratnasari Rustam; Jabaruddin; Karmila (Journal of Law, Social Science and Management, 2024)
Introduction: Overview: The death penalty is a crucial component of Indonesian law enforcement. Maintaining a retributive effect as a punishment for the wrongdoing done is another goal of the death sentence. The death penalty has been changed as an alternative punishment in an attempt to uphold human rights, even though it is still the primary punishment specified in the Criminal Code. This suggests a change in Indonesia's criminalization philosophy, which places a greater emphasis on initiatives to uphold human rights. In order to balance the legal interests of human rights defenders, the death penalty has been designated as an alternative punishment. Objective: The purpose of this paper is to clarify the normative clauses pertaining to the application of the death penalty in several criminal law statutes, both inside and outside the Criminal Code. Retributive justice is still the foundation of criminalization in Indonesia, which contributes to the poor level of human rights protection and respect in the nation. Methods: A legal, conceptual, and case approach are all utilized in this normative research methodology. Results: The adoption of the death penalty as a substitute form of punishment is anticipated to support future improvements in Indonesia's human rights compliance. The teachings of the Modern School and the Teleological Theory of criminal law are in line with the death penalty as an alternative punishment since it provides a compromise to resolve the death penalty controversy in the framework of human rights. Keywords: Death Penalty, alternative, Human Rights